2018
DOI: 10.1016/j.geomorph.2018.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Can glacial shearing of sediment reset the signal used for luminescence dating?

Abstract: Understanding the geomorphology left by waxing and waning of former glaciers and ice sheets during the late Quaternary has been the focus of much research. This has been hampered by the difficulty in dating such features. Luminescence has the potential to be applied to glacial sediments but requires signal resetting prior to burial in order to provide accurate ages. This paper explores the possibility that, rather than relying on light to reset the luminescence signal, glacial processes underneath ice might ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Our results demonstrate that the OSL signal decreases drastically during high‐velocity friction experiments. Previous studies showed that the TL and OSL intensities of quartz grains decrease (or locally become zero) after slow slip rate ( V = 16 to 56 μm s −1 ) experiments (Bateman et al, 2018; Hiraga et al, 2004). Hiraga et al (2004) identify a reverse relationship between TL intensity and applied frictional work.…”
Section: Discussionmentioning
confidence: 98%
“…Our results demonstrate that the OSL signal decreases drastically during high‐velocity friction experiments. Previous studies showed that the TL and OSL intensities of quartz grains decrease (or locally become zero) after slow slip rate ( V = 16 to 56 μm s −1 ) experiments (Bateman et al, 2018; Hiraga et al, 2004). Hiraga et al (2004) identify a reverse relationship between TL intensity and applied frictional work.…”
Section: Discussionmentioning
confidence: 98%
“…Infra-red stimulated luminescence (IRSL) dating on sheared deposits Although predominantly carbonate, TSS units may contain small amount of quartz and feldspar grains. It has been shown in previous studies that the luminescence signal can be reset (called triboluminescence) by heating, mechanical crushing or shearing 37 processes in intense sheared bands such as frictionnites.…”
Section: Datingmentioning
confidence: 99%
“…Further inland, such as in mixing soils on hillslopes, bleaching occurs entirely by surface exposure where grains reach the surface via mixing processes and are then reburied (Reimann et al, ). Finally, in rare cases, bleaching can potentially occur via mechanisms such as pressure at the bottom of a glacier (Bateman et al, ). The wide variety in the extent of bleaching, and our limited understanding of the processes, shows that much is yet to be learned about the connections between luminescence and geomorphology.…”
Section: Luminescence and Its Characteristics In Geomorphic Environmentsmentioning
confidence: 99%